Climate Change, new Metanarrative for Humanity : Climate Policy in the western Mediterranean - Camargo Ribeiro Marques dos Santos, João (2020)
“Why is there not an adequate and efficient answer to climate change?” is a question that has been haunting millions of people around the world for the last decades, and that is growingly being made by all publics. Despite the scientific consensus on climate change, the necessary measures to deter this phenomenon are still far from the speed and range necessary to effectively address it (when there are any measures at all). Metanarratives are the grand histories that humankind tells itself to guide its practices and actions. They either work towards solving this civilisational crisis or to stop any effective solutions. The current metanarrative of globalised capitalist positivism is one of the main obstacles to stopping the climate crisis, but there is a conflict of metanarratives in the world today, and new possibilities are coming into existence. Potential future metanarratives for a different climate will either be survival of the fittest or civilising tools when human civilisation is in its most dangerous moment. The current metanarrative underpins capitalist dominance and is perpetuated through capitalist ideology and hegemony, locking humanity into a path of irreversible climate change. The unavoidable systematic change needed to effectively tackle climate change will go as deep as the social construction of what “human nature” is and what relations humans have to each other and the environment. Through an adaptation of Michael Burawoy’s extended case method a methodology has been developed to evaluate the appearance of a new climate change metanarrative articulated with social justice, a climate justice potential metanarrative. A historical study on the evolution of public policy and climate policy in particular for three countries in the western mediterranean - Portugal, Spain and Morocco - was conducted. A revision of information about each of the countries, focusing on the evolution of climate and future scenarios, as well as social, economical, political and industrial tendencies, was done. There were 1107 interviews conducted for this thesis, 46 of which were face-toface and structured. A methodological tool was developed to quantify the difference between really existing climate policy and climate action that would achieve the affirmed goals of stopping climate collapse on the three countries. Over the course of three years post-Paris Agreement enquiries were conducted in Portugal (in the ClimAdaPT.local project), in Spain and Morocco, focusing on national and local politicians, academia, social movements and private enterprises. From believing into climate change until supporting effective climate policies, there is a long path where world views, political affiliation and ideology, cultural values, perception of risks, experiencing climate change, notions of international and social justice, attribution of responsibilities and public participation play a very important role. The inquiries revealed that many personal and collective blocks are determinant in the path into reaching policies that effectively respond to the climate crisis, and that shifting world views and experiences that affect this path will be tested in the coming years. This is a qualitative expression of the current metanarrative of globalised capitalist positivism and the political clashes of the present moment open the door to new metanarratives, including a potential metanarrative of climate justice. Together with other researchers ‘climate policy gap’ graphics were developed for Portugal, Spain and Morocco to help reveal this divide and quantify the under-reaction between diagnosis and action, through layers of political indecision, mis-communication, insufficient action and the power of the fossil fuels industries. The climate policy gaps for the three nations revealed overshoots on even the most ambitious levels of emissions reductions pledged when compared to trajectories compatible with 1.5ºC or 2ºC limits. This research suggests that there is a built-in feature of under-reaction in climate policy, which staves off any emission pathways compatible with stopping a temperature rise above 1.5ºC by 2100. The climate policy gap is a political and methodological tool that reveals systemic shortcomings of climate action, its visibility identifies benchmarks and sectors that should be activated to close these gaps in response to the growing popular demands for climate justice and it quantifies the gap between a metanarrative of globalised capitalist positivism and what is necessary to prevent reaching even the Paris Agreement’s targets. 2018 and 2019 saw the emergence of a much stronger climate justice movement. The three most relevant components of this movement - Blockadia, Youth Climate Strikes (Fridays for Future) and Extinction Rebellion - have combined efforts in a global call for civil disobedience and insurgency on political lines that respond to the climate science that calls for a 50% greenhouse gas global cuts by 2030. They have put in the forefront the issue of social justice. Growingly radical Green New Deals' versions and campaigns such as Climate Jobs are creating political programs for a social revolution in line with German jewish philosopher Walter Benjamin’s idea of revolution as the emergency break when history moves in a catastrophic direction. An early critic of the dangers posed by the threats of progress and technological development led by capitalism, Benjamin proposed an alternative view of revolution: it is not inevitable or a natural result of the contradiction between productive forces and productive relations, but rather an interruption of an historical evolution that is leading to catastrophe. These movements and programs are not enough for the emergence of a new climate justice potential metanarrative, although they are necessary conditions for it. In conclusion, there are signs of the emergence of a climate justice potential metanarrative, with a push for the creation of new institutions, adaptation of old ones, public perception of the dimension of the problem of climate change and effective legislative response to it. Some of the most expressive characteristics of this potential metanarrative were outlined: a human awakening full of impetus for social reordering; a redistribution of power, wellbeing and cooperation; a new notion of prosperity inside natural limits and just resource redistribution; reconnection of knowledges and sciences; the need for a public and participatory science to address human’s and earth’s needs; the teleology of humanity’s collective survival; understanding and respecting life system’s cycles, favouring life’s diversity as an efficient tool against the current increase in entropy in the ecosphere; acknowledging and integrating the care economy into daily life, with the coresponsibilization of men and women for care and maintenance activities; recovering indigenous people’s knowledge of biomimicry as a collective tool, promoting human beneficial effects on life cycles and ecosystems; understanding capitalist production’s incompatibility with basic life system’s principles. A new potential metanarrative for climate change is a historical novelty, but only such a novel Grand History can give humanity a chance to overcome the biggest threat it has ever faced.